Application Of Innovation In Marketing Strategies For Sustainable Tourism In Raja Ampat - Astuti, Ni Luh Gde Sari Dewi; Sunny, Milla Permata; Suharyati, Suharyati; Nasfi, Nasfi; Sofyan, Hady (Jurnal Ilmu Sosial Mamangan, 2025)
Raja Ampat, located in Southwest Papua, Indonesia, is known as a paradise for divers and nature lovers with its extraordinary underwater and land natural beauty. This archipelago consists of more than 1,500 small islands surrounded by four main islands: Misool, Salawati, Batanta, and Waigeo. As part of the Coral Triangle, Raja Ampat is a center of marine biodiversity with hundreds of unique and endangered species. The name "Raja Ampat" comes from a local legend about four kings who occupied the four largest islands. Apart from its natural beauty, Raja Ampat also focuses on environmental conservation through its Marine Protected Area Network which covers more than 4 million hectares. Sustainable tourism is a major concern in Raja Ampat to maintain beauty and biodiversity. This involves digital marketing through social media, collaboration with influencers, and the adoption of sustainable technology. Challenges faced include a lack of tourist awareness, limited infrastructure, and low local community participation. This research uses qualitative methods through case studies, semi-structured interviews, and participant observation to understand the application of innovation in sustainable marketing strategies. Through appropriate marketing strategies, Raja Ampat seeks to attract tourists who support sustainable tourism, ensuring its natural beauty is maintained for future generations.